Harvesting Environment Mechanical Energy by Direct Current Triboelectric Nanogenerators - Chuncai Shan; Kaixian Li; Yuntao Cheng; Chenguo Hu (Nano-Micro Letters, 2023)
Highlights The basic theory, key merits and potential development of direct current triboelectric nanogenerator (DC-TENG) from the aspect of mechanical rectifier, tribovoltaic effect, phase control, mechanical delay switch and air-discharge are discussed in detail. This review provides a guideline for future challenges of DC-TENGs, and a strategy for improving the output performance for commercial applications.